2020
DOI: 10.1371/journal.pone.0232912
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Raman microscopy to identify bacteria in oral subgingival biofilm models

Abstract: The study of oral disease progression, in relation to the accumulation of subgingival biofilm in gingivitis and periodontitis is limited, due to either the ability to monitor plaque in vitro. When compared, optical spectroscopic techniques offer advantages over traditional destructive or biofilm staining approaches, making it a suitable alternative for the analysis and continued development of three-dimensional structures. In this work, we have developed a confocal Raman spectroscopy analysis approach towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…We detected various bacterial taxa typically present in the oral (Streptococcus dentisani [ 60 ]; Streptococcus intermedius [ 61 ]; Fusobacterium nucleatum [ 62 ]; Prevotella spp. [ 63 ]) and intestinal microflora (Barnesiella intestinihominis [ 64 ]; Porphyromonadaceae [ 65 ]). In addition, we observed the genus Phenylobacterium, which was reported to be present in the middle ear [ 66 ], putatively being a commensal of the upper aerodigestive tract.…”
Section: Resultsmentioning
confidence: 99%
“…We detected various bacterial taxa typically present in the oral (Streptococcus dentisani [ 60 ]; Streptococcus intermedius [ 61 ]; Fusobacterium nucleatum [ 62 ]; Prevotella spp. [ 63 ]) and intestinal microflora (Barnesiella intestinihominis [ 64 ]; Porphyromonadaceae [ 65 ]). In addition, we observed the genus Phenylobacterium, which was reported to be present in the middle ear [ 66 ], putatively being a commensal of the upper aerodigestive tract.…”
Section: Resultsmentioning
confidence: 99%
“…We detected various bacterial taxa typically present in the oral [Streptococcus dentisani 55 ; Streptococcus intermedius 56 ; Fusobacterium nucleatum 57 ; Prevotella spp. 58 ] and intestinal micro ora [Barnesiella intestinihominis 59 ; Porphyromonadaceae 60 ]. In addition, we observed the genus Phenylobacterium, reported to be present in the middle ear 61 , putatively being a commensal of the upper aerodigestive tract.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous publication by the same authors, a ThermoFisher Scientific DXR2xi instrument was used for acquisition. Renishaw inVia Qontor was used in this research because of its increased specificity and signal count compared to the ThermoFisher Scientific DXR2xi, thus being able to show minor bands (Kriem et al, 2020). The instrument was equipped with a 532 nm filter and a 532 nm laser to capture a spectral range of 282.8-2016.2 cm −1 and 1,015 collection points.…”
Section: Raman Data Acquisition Processing and Microscopic Imagingmentioning
confidence: 99%
“…Bacteria in subgingival biofilms occupy the same habitat and, therefore, show similar chemical compositions. We previously demonstrated that differentiation between species can be successfully achieved using spectral fingerprint patterns and multivariate statistical models for five subgingival species from four different "Socransky complexes" (Socransky et al, 1998;Kriem et al, 2020). Additionally, we successfully determined and differentiated mono-species biofilms based on their spectral fingerprint region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation